124k views
0 votes
For which equation will f(-2)= -6?

For which equation will f(-2)= -6?-example-1

2 Answers

0 votes

Answer:the correct option is C

Explanation:

To find the equation for which

f(-2) = - 6, we will substitute x = - 2 into each of the equations. It becomes

A) f(x) = -2^3 + (-2) = - 8 - 2 = -10

B) f(x) = (-2)^4 -5(-2) = 16 + 10 = 26

C) f(x) = 4x^3 + 6x^2 - x = 4(-2)^3 + 6(-2)^2 - (-2) = (4 × -8) + (6 × 4) + 2

= - 32 + 24 + 2 = - 6

D) f(x) = - 3(-2)^3 - 4(-2)^2 + 4(-2) = (-3 × - 8) - (4 × 4) + (4 × -2) = 24 - 16 - 8 = 0

Therefore, the correct option is C

User Ellabeauty
by
5.5k points
1 vote

Answer:

C.
f(x)=4x^3+6x^2-x

Explanation:

Lets plug in -2 into each of these equation to see which one gives us the solution of -6

A.
f(x)=x^3+x


f(-2)=(-2)^3+(-2)\\\\f(-2)=-8-2\\\\f(-2)=-10

B.
f(x)=x^4-5x


f(-2)=(-2)^4-5(-2)\\\\f(-2)=16+10\\\\f(-2)=26

C.
f(x)=4x^3+6x^2-x


f(-2)=4(-2)^3+6(-2)^2-(-2) \\\\f(-2)=4(-8)+6(4)+2\\\\f(-2)=-32+24+2\\\\f(-2)=-6

D.
f(x)=-3x^3-4x^2+4x


f(-2)=-3(-2)^3-4(-2)^2+4(-2)\\\\f(-2)=-3(-8)-4(4)-8\\\\f(-2)=24-16-8\\\\f(-2)=0

As we can see, function C was the only one that gave us the value of -6, so that is our answer.

User Mazin Ibrahim
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.